Enhancing Biomass and Lutein Production From Scenedesmus almeriensis: Effect of Carbon Dioxide Concentration and Culture Medium Reuse - Molino, Antonio; Mehariya, Sanjeet; Iovine, Angela; Casella, Patrizia; Marino, Tiziana; Karatza, Despina; Chianese, Simeone; Musmarra, Dino (Frontiers in Plant Science, 2020)
The main purpose of this study is to investigate the effects of operative parameters and bioprocess strategies on the photo-autotrophic cultivation of the microalgae Scenedesmus almeriensis for lutein production. S. almeriensis was cultivated in a vertical bubble column photobioreactor (VBC-PBR) in batch mode and the bioactive compounds were extracted by accelerated solvent extraction with ethanol at 67°C and 10 MPa. The cultivation with a volume fraction of CO2 in the range 0–3.0%v/v showed that the highest biomass and lutein concentrations – 3.7 g/L and 5.71 mg/g, respectively – were measured at the highest CO2 concentration and using fresh growth medium. Recycling the cultivation medium from harvested microalgae resulted in decreased biomass and lutein content. The nutrient chemical composition analysis showed the highest consumption rates for nitrogen and phosphorus, with values higher than 80%, while sulfate and chloride were less consumed.